Persistent Superconductivity and Enhanced Photovoltaic Effect in YBCO Thin Films under Laser Irradiation (2024)
The study of YBCO thin films under laser irradiation reveals a significant interplay between their electrical and optical properties. Despite being exposed to energies exceeding the superconducting gap, YBCO retains its superconductivity and shows unexpected resilience. This, together with the photovoltaic effect induced by laser light, opens up possibilities for YBCO-based devices beyond current limits. YBCO thin films were fabricated on SrTiO3 substrates and exhibited a high critical temperature of 88 K. The superconductivity was minimally affected by the applied currents and pulsed laser irradiation, demonstrating its remarkable resilience. In addition, residual resistance and a photovoltaic effect were observed, revealing unique electronic properties. Reflectance measurements have highlighted the significant role of superelectrons in the optical response of YBCO. These findings have the potential to facilitate the development of novel and innovative YBCO-based devices, such as light-modulated superconductors and efficient solar cells.